Advanced training scenarios for liver surgery with realistic interactive 3D-printed phantoms (Transactions on Additive Manufacturing Meets Medicine, 2021)
Realistic surgery phantoms possess the potential to improve medical training and as a result improve surgery outcomes, reduce operation time and minimize patient risks. In this work, we developed a training scenario within visceral surgery, implementing lifelike liver phantoms using a hybrid manufacturing approach combining collagen-based casting and 3D-printing. Being equipped with integrated sensors, we developed a feedback system to assess the performance of the trained procedure. This could lead to a new paradigm within visceral surgery training.
Keywords: 3D-printing; Phantoms; Visceral surgery; liver phantom; Trainings scenario; realistic phantom